Discussão dos processos de encouraçamento de leitos fluviais (bed armouring) na perspectiva geomorfológica: o caso do rio Conceição – Quadrilátero Ferrífero/MG - Guilherme Eduardo Macêdo Cota (2019)
River-bed armouring processes refer to the presence of immobile (or immediately immobile) sediments in river channels, preventing the removal of potentially transportable grains. The detrital pavements (clusters) formed on the river-bed surface offer strong resistance to abrasive processes. This subject, despite being widely discussed in international literature, presents few studies and contributions at the national level. Overall, research on river-bed armouring mostly use hydrological criteria to determine the flow conditions for the disruption of detrital pavements, instead of following geomorphological approaches regarding the impacts of the clusters on river morphology and morphodynamics. In order to contribute to the studies on river-bed armouring in Brazil, this work intends to o investigate the occurrence of river-bed armouring, based on a systematization of theoretical bases, from a geomorphological perspective. Therefore, the Conceição River (Iron Quadrangle - MG) is used as case study. Based on cartographic techniques, observation and checklist-based descriptions, we proceeded to connect the impacts of the presence of detrital pavements to geomorphological conditions of the river channel, especially regarding the morphology and morphodynamics of the studied river sections. Channel material organization identified in the Conceição River points to the occurrence of the river-bed armouring processes from the confluence with Ribeirão Preto on, in which detrital pavements interspersed by pools occur, forming the morphology of riffle-pools. The flow conditions do not allow a linear arrangement of the clusters along the Conceição River, creating the morphology of riffle-pools and, possibly, meandering processes. It is noteworthy that there is a tendency for formation of detrital pavements in portions of the longitudinal profile with a predominance of aggradation processes, which provide stability to materials. There is also the occurrence of ferruginous armor in the bed, which performs the role of armouring the fluvial channel in a stronger way, as they do not depend on the flow regime, but on the electrochemical conditions that keep the material cohesive. In addition, reflections were made on the genesis of the clusters, highlighting the role river piracy in supplying detrital material to the Conceição River channel.